Advances in large amplitude oscillatory shear Rheology of food materials - Erturk, Merve Yildirim; Le, Anh Nghi Minh; Kokini, Jozef (Frontiers in Food Science and Technology, 2023)
Molecular interactions determine the microstructure of food, as well as its response to deformation and flow. In order to design efficient processing equipment, to produce high-quality, stable end products, to predict textural and sensory properties, and to ensure consumer acceptance, the characterization of food rheology is essential. Deformations are rapid and large during the processing of foods and during consumption. In food studies, large amplitude oscillatory shear (LAOS) has become increasingly popular due to its ability to mimic real-life processes. When food is subjected to dynamic oscillatory shear tests, a sinusoidal deformation is applied, the mechanical stress (or strain) is probed, and the response is recorded. This chapter summarize main methods to extract meaningful rheological parameters from complex LAOS response of selected food materials. A time-resolved nonlinear rheology method, sequence of physical processes (SPP), gave detailed interpretations of transient microstructures, whereas the Fourier Transform coupled with Chebyshev decomposition (FTC) method provide static measurements at specific strains. LAOS behavior and its relationship to food microstructures and texture still needed to be studied in depth. By constructing more accurate mechanical models of complex food systems, the fundamental knowledge can be applied to evaluate the nonlinear rheology of food for consumer acceptance and efficient processing.